Mean Antarctic Circumpolar Current Transport Measured in Drake Passage - Donohue, K. A.; Tracey, K. L.; Watts, D. R.; Chidichimo, María Paz; Chereskin, T. K. (Geophysical Research Letters)
The Antarctic Circumpolar Current is an important component of the global climate system connecting the major ocean basins as it flows eastward around Antarctica, yet due to the paucity of data it remains unclear how much water is transported by the current. Between 2007 and 2011 flow through Drake Passage was continuously monitored with a line of moored instrumentation with unprecedented horizontal and temporal resolution. Annual mean near-bottom currents are remarkably stable from year to year. The mean depth-independent, or barotropic transport, determined from the near-bottom current meter records was 45.6 Sv with an uncertainty of 8.9 Sv. Summing the mean barotropic transport with the mean baroclinic transport relative to zero at the seafloor of 127.7 Sv gives a total transport through Drake Passage of 173.3 Sv. This new measurement is 30% larger than the canonical value often used as the benchmark for global circulation and climate models. Fil: Donohue, K. A. University Of Rhode Island; Estados Unidos Fil: Tracey, K. L. University Of Rhode Island; Estados Unidos Fil: Watts, D. R. University Of Rhode Island; Estados Unidos Fil: Chidichimo, María Paz. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Defensa. Armada Argentina. Servicio de Hidrografía Naval; Argentina. Universidad de Buenos Aires; Argentina Fil: Chereskin, T. K. University of California at San Diego. Scripps Institution of Oceanography; Estados Unidos